Social responsibility aspects supporting the success of SPI. Issue 3 (30th April 2013) - Messnarz, Richard; Sicilia, Miguel‐Angel; Biro, Miklos; García‐Barriocanal, Elena; Garre‐Rubio, Miguel; Siakas, Kerstin; Clarke, Adrienne; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
ABSTRACT Software Process Improvement (SPI) activities aim at driving change in information technology development towards increased quality and productivity levels. The SPI Manifesto describes the key values and principles for a successful implementation of SPI. About two‐thirds of its principles relate to human, social, and organizational aspects and one‐third to technical aspects. This raises the question if these aspects have a relationship with 'social responsibility' principles. The new ISO 26000:2010 standard provides guidance about social responsibility (SR), describing the core subjects and issues an organization has to consider when implementing SR. In this paper, we describe how the values and principles of the SPI Manifesto have a relationship with the SR issues described in the ISO 26000. In addition, this paper describes about the steps taken in an industry group to exchange best practices about how social strategies can be used to achieve higher acceptance and sustainability of SPI initiatives. Copyright © 2013 John Wiley & Sons, Ltd.